Educating older people: From victimisation to safety on the internet - Miljković Jovan; Manić Ljiljana; Ljujić Bojan (Temida)
This paper examines older people’s vulnerability to cybercrime and education as a societal intervention to boost their safety and mitigate victimisation. The study presents the findings of the empirical research conducted with the aim of exploring the connection between certain bio-socio-educational features of older people, their perceptions, habits and experiences in the domain of Internet safety. This descriptive research focuses on the sample drawn from older adults in the Republic of Serbia. Findings show that the respondents access the Internet daily on multiple occasions, thereby facing potential risks in the virtual realm where they lack knowledge regarding safe online practices. Some rely on antivirus programmes for protection, while others have no protection. The research reveals that primary threats to older people’s safety are unauthorised retrieval of personal data and disruption of device functionality due to computer virus infiltration.